2020
DOI: 10.1111/jfb.14262
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting life‐history traits of two sympatric smooth‐hound species: implication for vulnerability

Abstract: In this study, life‐history traits (maximum and average size, size at maturity and fecundity) of two congeneric smooth‐hounds, Mustelus mustelus and Mustelus punctulatus, which share a geographical distribution and experience a similar fishing exploitation, were estimated and compared between species. The results indicated a lower maximum and average size, a lower size at maturity and a higher fecundity in M. punctulatus compared with those in M. mustelus. Considering that these two species co‐occur in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Due to its sedentary habits, S. canicula resides in the northwestern Adriatic Sea throughout the year [33], although some sexual segregation occurs in the study area, as also reported in other populations [33][34][35]. The two Mustelus species are large (up to 158 and 141 cm for M. mustelus and M. punctulatus, respectively; [36]) viviparous species that reach sexual maturity at large sizes (110-120 cm [36]) and share very similar morphology, life history traits [36,37], and habitats. These congeneric species have a demersal habit and spend most of the time swimming in midwater or, more commonly, near the bottom, down to a depth of 350 m [30].…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…Due to its sedentary habits, S. canicula resides in the northwestern Adriatic Sea throughout the year [33], although some sexual segregation occurs in the study area, as also reported in other populations [33][34][35]. The two Mustelus species are large (up to 158 and 141 cm for M. mustelus and M. punctulatus, respectively; [36]) viviparous species that reach sexual maturity at large sizes (110-120 cm [36]) and share very similar morphology, life history traits [36,37], and habitats. These congeneric species have a demersal habit and spend most of the time swimming in midwater or, more commonly, near the bottom, down to a depth of 350 m [30].…”
Section: Introductionsupporting
confidence: 64%
“…We considered size rather than sexual maturity because, in elasmobranchs, size accounts for dietary ontogenetic shifts and predatory abilities [7,69]. The mean total length observed in the northern Adriatic Sea (males and females combined: 41.5, 92.9, and 76.1 cm for S. canicula, M. mustelus, and M. punctulatus, respectively; [33,36]) was used as a threshold to allocate individuals to the big-or the small-sized group. Species sampled during spring or summer (March-August) were allocated to the warm season group, while those sampled during autumn or winter (September-February) were allocated to the cold season group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the different factors affecting the retention pattern have to be understood to assess species specific vulnerability. Large scale studies usually do not take into consideration the relative vulnerability of species within a complex or a multispecific fishery (Riginella et al, 2020). In these situations, Rajidae' vulnerability is not only dependent on their own species-specific life history traits, but also of their relative vulnerability to the species they are managed with.…”
Section: Retention Pattern Causesmentioning
confidence: 99%